El procedimiento contencioso administrativo - Piedra García, Pedro Audelo (2015)
The purpose of the present investigation was to examine a topic little studied, of which have had interests in knowing the state of the knowledge evidenced through the revision of the literature, as well as the orientation and reach given to the investigation. The project of the investigation defined as general objective: to carry out a juridical study on the contentious administrative procedure as resource to guide the rights of the public servants, the administrative acts emanated by the organs and entities of the public sector, the origin of the contentious administrative jurisdiction and the contentious resources foreseen in the law, analyzing their antecedents, characteristic, elements, etc. As specific objectives they were determined: to make an analysis of inherent contents to the public administration and the administrative acts emanated by the organs and entities of the public sector; to examine the reach of the Law of the Contentious Administrative Jurisdiction in the solution of conflicts of the public servants and finally to observe the procedural aspects of the contentious administrative resource. Considering that the nature of the investigation was fundamentally of documental, empiric and procedural revision, he/she began carrying out a wide analysis from the bibliographical relative references to the contentious administrative process. After the phase of storing of the documental references you proceeded to select those contents of interest and relevancy with the investigation topic. The fundamental base of the study and analysis constituted it the Law of the Contentious Administrative Jurisdiction, juridical instrument that regulates the contentious administrative procedure, and their normative one related: Constitution of the Republic of Ecuador, Organic Law of the Public Service, Regulation to the Organic Law of the Public Service, Law of the Contentious Administrative Jurisdiction, Statute of the Juridical and Administrative Régime of the Executive Function. A study is also included in the field of the compared right and in the procedural aspect he/she took a case of study of the Ecuadorian jurisprudence. In the part of results, in consideration of the nature of the investigation, it consists step-by-step the development of the contentious administrative procedure. For object of their academic study we divide it in three stages: initial, probatory and resolutory. To each one of them has developed it to him making a comparative analysis with a subjected case study to knowledge of a Tribunal Administrative Distrital of the Contentious thing. The study of selected case was processed before the Tribunal Distrital of the Administrative Contentious N° 4 of Portoviejo, trial N° 191-2006, with respect to the interference of a resource subjective or full jurisdiction of a public servant that was deprived of its position. As conclusions we should indicate that the investigation was developed in two segments: A theoretical part of the right noun and doctrinal, in which is analyzed the relating contents to the public administration, the public servants, the administrative acts emanated by the administrative organs, etc.; and a procedural part where the contentious administrative jurisdictional process was examined and particularly the step of the resource contentious office worker foreseen in the Law of the Contentious Administrative Jurisdiction. With relationship to the step of the procedure contentious office worker foreseen in the law of the Contentious Administrative Jurisdiction, we consider that in the practice it is not completed taking into account the dispositions consecrated by the articles 192 and 194 of the Political Constitution of the Republic that institute the implementation of a summary process guaranteeing the immediacy, the velocity and the efficiency in the administration of justice and to settle down the oral system. The dispositions of the Law of the Jurisdiction Contentious Office worker are diffuse. This lack of clarity has generated multiple inconveniences, what has allowed to those administered to deduce multiple actions before the Tribunals Distritales, that which has impacted in the accumulation of causes, generating chaos in the administration of justice